PENERAPAN PRINSIP-PRINSIP TATA KELOLA PERUSAHAAN YANG BAIK DARI PERSPEKTIF ETIKA BISNIS ISLAM - Widya Andryani; Baiq El Badriati; Umu Rosyidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article explores the implementation of Good Corporate Governance (GCG) principles from the perspective of Islamic business ethics. The study emphasizes how the foundational values of Islam—such as justice, accountability, trust (amanah), transparency, and responsibility—align with modern GCG frameworks. Using a qualitative literature study approach, this article examines academic journals, books, and regulatory documents that discuss intersections between Islamic ethics and corporate governance practices. The findings indicate that Islamic ethical principles substantially reinforce the integrity and effectiveness of GCG implementation in organizations, especially those operating within Islamic economic frameworks.